IMPLEMENTASI PERATURAN DAERAH KABUPATEN PANDEGLANG NOMOR 10 TAHUN 2011 TENTANG RETRIBUSI JASA UMUM (Studi kasus Retribusi Pelayanan Persampahan/Kebersihan Di Pasar Pandeglang) - Neng Rohiyah Neng Rohiyah; Jumanah Jumanah (LPPM STIA Banten, 2018)
This research is intended to find out and analyze the Implementation of Regulations Pandeglang Regency Area Number 10 of 2011 Concerning Public Service Retribution (Study The Case of Garbage/Cleaning Retribution at Pandeglang Market). Based on observation Initially there are several indications of problems as follows; (1) There is a discrepancy the amount of levy rates imposed; (2) There are no sanctions; (3) Lack of openness information; (4) Lack of facilities and infrastructure which include trash cans, trash bins, and the street in Pandeglang Market. Awareness of traders and buyers in habits throw garbage; (5) Lack of commitment and discipline of officers cleanliness. The method in this study is a qualitative approach, with using data validity and data analysis. The results of this study indicate that implementation of Pandeglang Regency Regional Regulation number 10 of 2011 concerning Public Service Retribution where one of which is regulated in the policy is Garbage/cleaning service retribution has not been implemented properly. Suggestions in this study include (1) the improvement and supervision of tariff implementation service fees; (2) the need for disclosure of information regarding service fees waste, and (3) increasing the number of janitors.